Exploring how levetiracetam mitigates toxicity and ameliorates memory impairment - Alhowail, Ahmad H.; Alharbi, Abeer M. (Frontiers in Pharmacology, 2025)
Cognitive impairment encompasses a spectrum of deficits that markedly affect daily functioning and quality of life. Understanding the specific cognitive domains involved is thus crucial for developing targeted interventions and effective support strategies. This impairment ranges from mild cognitive decline to severe dementia and disproportionately affects older adults and cancer survivors. Multiple pathophysiological mechanisms, including elevated neuroinflammation, oxidative stress, disrupted synaptic plasticity, and neuronal apoptosis, contribute to the onset and progression of cognitive dysfunction. Emerging clinical and experimental data suggest that pharmacological interventions, including levetiracetam (LEV), a second-generation antiepileptic drug, can attenuate cognitive impairment. The neuroprotective potential of LEV is attributed to its unique mechanism of action, which involves selective binding to synaptic vesicle protein 2A and modulation of neurotransmitter release. In addition to its well-established antiepileptic effects, LEV exhibits anti-inflammatory and antioxidant properties, suggesting broader therapeutic applications in mitigating cognitive decline. This review synthesizes current knowledge on the mechanisms underlying cognitive impairment, evaluates existing measurement and prevention approaches, along with their limitations, and critically examines the potential efficacy of LEV in this context. The novelty of this review lies in its integrative focus on the mechanistic pathways through which LEV may protect against cognitive decline, with attention to conflicting findings and unresolved questions. In conclusion, current evidence suggests that LEV is a promising therapeutic candidate beyond epilepsy, though further clinical studies are needed to confirm its efficacy.